2015
DOI: 10.1039/c5ra06654a
|View full text |Cite
|
Sign up to set email alerts
|

Dual amplifying fluorescence anisotropy for detection of respiratory syncytial virus DNA fragments with size-control synthesized metal–organic framework MIL-101

Abstract: Nanosized MIL-101 with negligible scattered light, synthesized by the addition of glycerol, was used to amplify FA for the detection of DNA with a dual amplification effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…MOFs with advantages of large specific surface area, high porosity, fluorescence quenching, high loading efficiency, easy functionalization, and tunable pore size ( Agostoni et al, 2015 ; Li et al, 1999 ; Rowsell and Yaghi, 2004 ) have gained considerable attention in many aspects, such as adsorption ( Ghanbari et al, 2020 ), separation ( Tang and Tanase, 2020 ), catalysis ( Li et al, 2019a ), energy storage ( Li et al, 2020a ), biosensing and bioimaging ( Carrasco, 2018 ; Li et al, 2020b ; Wang, 2017 ; Yang et al, 2019a ), drug delivery ( He et al, 2019b ; Wang et al, 2020a , Wang et al, 2020b ; Wu and Yang, 2017 ; Yang et al, 2018 ; Zhang et al, 2020a ; Zhong et al, 2019 ), cancer immunotherapy ( Zhong et al, 2019 ; Zhong and Sun, 2020 ), etc. Among them, biosensing is a promising direction with the following advantages: (1) large specific surface areas and high porosity for probe adsorption and fluorescence quenching ( Luo et al, 2020b ); (2) adjustable pores with particular shape and sizes via building blocks with different lengths ( Deng et al, 2012 ); (3) the selectivity enabled by the specific pore size allowing small molecules enter while excluding large molecules ( Guo et al, 2015 ); (4) the abundant functional groups and positively charged metal ions provide various interactions, such as electrostatic interactions, hydrogen bonding, and π-π stacking for adsorption of fluorophore-labeled probes ( Zhang et al, 2014a ); ( Fig. 1 ) (5) the reduced background fluorescence signals and enhanced sensitivities by MOFs ( Fang et al, 2014 ; Qin et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MOFs with advantages of large specific surface area, high porosity, fluorescence quenching, high loading efficiency, easy functionalization, and tunable pore size ( Agostoni et al, 2015 ; Li et al, 1999 ; Rowsell and Yaghi, 2004 ) have gained considerable attention in many aspects, such as adsorption ( Ghanbari et al, 2020 ), separation ( Tang and Tanase, 2020 ), catalysis ( Li et al, 2019a ), energy storage ( Li et al, 2020a ), biosensing and bioimaging ( Carrasco, 2018 ; Li et al, 2020b ; Wang, 2017 ; Yang et al, 2019a ), drug delivery ( He et al, 2019b ; Wang et al, 2020a , Wang et al, 2020b ; Wu and Yang, 2017 ; Yang et al, 2018 ; Zhang et al, 2020a ; Zhong et al, 2019 ), cancer immunotherapy ( Zhong et al, 2019 ; Zhong and Sun, 2020 ), etc. Among them, biosensing is a promising direction with the following advantages: (1) large specific surface areas and high porosity for probe adsorption and fluorescence quenching ( Luo et al, 2020b ); (2) adjustable pores with particular shape and sizes via building blocks with different lengths ( Deng et al, 2012 ); (3) the selectivity enabled by the specific pore size allowing small molecules enter while excluding large molecules ( Guo et al, 2015 ); (4) the abundant functional groups and positively charged metal ions provide various interactions, such as electrostatic interactions, hydrogen bonding, and π-π stacking for adsorption of fluorophore-labeled probes ( Zhang et al, 2014a ); ( Fig. 1 ) (5) the reduced background fluorescence signals and enhanced sensitivities by MOFs ( Fang et al, 2014 ; Qin et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Chen and coworkers ( Zhu et al, 2013 ) first reported two dimensional (2D) MOF ([Cu(H 2 DTOA)] n ) which was utilized as a sensing platform for effective detection of thrombin and HIV-1 DNA sequences with high selectivity and sensitivity. Currently, MOF-based sensing technology has been gradually used for detecting various viruses, involving HIV ss-DNA ( Pan et al, 2018 ; Zhu et al, 2013 ), HIV ds-DNA ( Chen et al, 2013 ), respiratory syncytial virus ( Guo et al, 2015 ), Ebola virus ( Qin et al, 2016 ), Sudan virus ( Yang et al, 2015 ), Zika virus ( Xie et al, 2018 ), Dengue virus ( Xie et al, 2018 ), H 5 N 1 virus ( Wei, 2013 ), hepatitis A virus (HAV) ( Luo et al, 2020b ), etc. And extensive MOFs or MOF-derived porous carbon materials including UiO-66-NH 2 ( Zhang et al, 2014a ), ZIF-8 ( Pan et al, 2018 ), MIL-88B ( Tian et al, 2015 ), MIL-101 ( Yang et al, 2020 ), H 2 dtoaCu ( Ye et al, 2014 ), NiCo 2 O 4 embedded with carbon nanotubes (NiCo-MOF) ( Jia et al, 2019 ), etc., have been applied for virus detection.…”
Section: Introductionmentioning
confidence: 99%
“…The limit of detection was as low as 16.7 fM toward HIV-1 DNA. In addition, A chromium-benzenedicarboxylates (MIL-101) MOF was applied to monitor respiratory syncytial virus (RSV) gene sequences in a label-free technique relying on fluorescence anisotropy [ 152 , 153 , 154 , 155 ].…”
Section: Nanotechnology To Detect Sars-cov-2mentioning
confidence: 99%
“…Studies have been documented with MOFs including UiO-66-NH 2 , MIL-88B, H2dtoaCu, and MIL-101, which show tremendous abilities to bind with dye-labeled DNA, quenching its uorescence intensity. [28][29][30] NMOFs bind to dye-labeled ssDNA through electrostatic, p-p stacking, and/or hydrogen-bonding interactions. Therefore, the uorescence is quenched by photoinduced electron transfer (PET) and uorescence resonance energy transfer (FRET) mechanisms.…”
Section: Introductionmentioning
confidence: 99%